The Simplified Method of Head Stiffness Considering Semi-Rigid Behaviors of Deep Foundations in OWT Systems - Li, Wei; Li, Xiaojuan; Wang, Tengfei; Yin, Qian; Zhu, Mingxing (Buildings (Basel), 2024)
Simplified methods of static free head stiffness of the semi-rigid foundation under lateral loads were limited to flexible or rigid behavior by the critical length of piles. This would lead to errors when predicting the static or dynamic performance of their upper structures in OWT Systems. This paper presents a comprehensive analysis of the head static stiffness of the semi-rigid pile without considering the critical length. Firstly, case studies using the energy-based variational method encompassing nearly twenty thousand cases were conducted. These cases involved different types of foundations, including steel pipe piles and concrete caissons, in three types of soil: homogeneous soil, linearly inhomogeneous soil, and heterogeneous soil. Through the analysis of these cases, a series of polynomial equations of three kinds of head static stiffness, containing the relative stiffness of the pile and soil, the slenderness ratio, and Poisson’s ratio, were developed to capture the semi-rigid behavior of the foundations. Furthermore, the lateral deflection, the rotation for concrete caissons in the bridge projects, and several natural frequencies of three cases about the OWT system considering the SSI effect were carried out. the error of high-order frequency of the OWT system reached 13% after considering the semi-rigid effect of the foundation.